Harmonization of Molecular Testing for Non-Small Cell Lung Cancer: Emphasis on PD-L1 - Imyanitov, Evgeny N.; Ivantsov, Alexandr O.; Tsimafeyeu, Ilya V. (Frontiers in Oncology, 2020)
Harmonization of molecular testing for non-small cell lung cancer: emphasis on PD-L1